Bioinformatics of Non Small Cell Lung Cancer and the Ras Proto-Oncogene - Kashyap, Amita (Springer, 2015)
Cancer is initiated by activation of oncogenes or inactivation of tumor suppressor genes. Mutations in the K-ras proto-oncogene are responsible for 10–30% of adenocarcinomas. Clinical Findings point to a wide variety of other cancers contributing to lung cancer incidence. Such a scenario makes identification of lung cancer difficult and thus identifying its mechanisms can contribute to the society. Identifying unique conserved patterns common to contributing proto-oncogenes may further be a boon to Pharmacogenomics and pharmacoinformatics. This calls for ab initio/de novo drug discovery that in turn will require a comprehensive in silico approach of Sequence, Domain, Phylogenetic and Structural analysis of the receptors, ligand screening and optimization and detailed Docking studies.